Language and identity: the impact of a multilingual environment on the personal identity among German mother tongue speakers living in Malaysia - Majtanova, Miroslava; Abdul Jabar, Mohd. Azidan (Universiti Putra Malaysia Press, 2014)
Through 18 interviews with German mother tongue speakers living in Malaysia, we investigate the impact of a foreign language on the individual’s identity. In this context, the study relies on the Social Identity Theory and Social Categorisation Theory which focus on language and identity. The researchers were of the view that the use of a foreign language serves as a substitute for the mother tongue in the construal of identity only to a certain extent. This phenomenon becomes most apparent in situations where the competency of the language is crucial for the respondent involved in communication. Depending on the importance of the situation the respondents experience a different level of achievement/ failure in expressing their identity. At the same time, the respondents evaluate identity of their communication partner by rating their language skills. Our findings further indicate that language makes a linkage between personal and social identities which is reflected in the feelings and behaviour of respondents in situation, when they cannot understand the language others use around them. Additionally the individual’s identity perception does not seem to be influenced by the length of stay in Malaysia, nor by a long/short term relationship with a non-German speaking partner. The mother tongue however becomes replaceable, provided the respondent gained the knowledge in a certain area in a foreign language. In this case, the individual will have difficulty to communicate about that particular area in his mother tongue except with practice.